Kajian Semiotika Roland Barthes terhadap Simbol Perempuan dalam Al-Qur’an - Mulyaden, Asep (Hanifiya: Jurnal Studi Agama-Agama, 2021)
This article aims to examine the symbol of women in the Qur'an. Because women have always been discriminated against and have not received equality, to find answers from the Qur'an, the author looks for it with the semiotic approach of Roland Barthes, who holds that everything can be approached in two stages; namely the first stage is called the linguistic system and the second stage is called the mythical system (myth). In Barthes's view, Myth is assumed to be a signifying system built on three things: the signifier, the signified, and the sign. Based on Barthes' theoretical approach to the symbols of zauj, imra’ah, and women as queens, women and men have similarities and differences. In one case, they are the same, but in another, they are different. They have similarities in origin, namely both from land, similarity in status as humans, equality in terms of responsibilities, job eligibility, and the like. But in terms of duties and obligations, in terms of physical, mental both have differences.